A phase 2 study of first‐line nivolumab in patients with locally advanced or metastatic cutaneous squamous‐cell carcinoma. Issue 24 (24th October 2022) - Munhoz, Rodrigo R.; Nader‐Marta, Guilherme; de Camargo, Veridiana P.; Queiroz, Marcello M.; Cury‐Martins, Jade; Ricci, Hermínia; de Mattos, Marcela R.; de Menezes, Thiago A. F.; Machado, Guilherme U. C.; Bertolli, Eduardo; Barros, Milton; de Souza, Carina E.; et al.
Abstract : Background: Cutaneous squamous‐cell carcinoma (CSCC) is among the most frequent malignancies worldwide. For those not amenable to treatment with curative intent, immune checkpoint inhibition (ICI) with anti‐programmed death receptor 1 (PD‐1) antibodies has emerged as a novel therapeutic option. In this study, the authors sought to investigate the activity of the anti‐PD‐1 agent nivolumab in patients with advanced CSCC (aCSCC). Methods: CA209‐9JC was an open‐label, single‐arm, phase 2 study to evaluate the safety and/or efficacy of nivolumab in systemic treatment‐naive patients with aCSCC. Nivolumab (3 mg/kg) was administered every 2 weeks until disease progression, unacceptable toxicity, or 12 months of treatment. The primary end point was the best objective response rate (BORR) as per RECIST 1.1 criteria. Secondary end points included safety, progression‐free survival (PFS), and overall survival (OS). Results: Twenty‐four patients with aCSCC were enrolled with a median age of 74 years (range, 48–93). Among the 24 patients evaluable for response, the BORR was 58.3% (14/24); there were no complete responses. With a median follow‐up of 17.6 months, median duration of response has not been reached, and the estimated median PFS and OS were 12.7 and 20.7 months, respectively. Prior exposure to radiotherapy was associated with worse outcomes ( p  = .035, univariate analysis). Treatment‐related adverse events of any grade and grade ≥ 3 occurred in 21 (87.5%) and six (25%) patients, respectively, and one patient discontinued nivolumab due to toxicities. Conclusions: Nivolumab resulted in robust antitumor activity, sustained responses, and good tolerability in systemic treatment‐naive patients with aCSCC. These data provide further evidence to support the use of ICI as the standard treatment of aCSCC. Abstract : In CA209‐9JC, a single‐arm, phase 2 study, 24 systemic treatment‐naive patients with advanced cutaneous squamous‐cell carcinoma were treated with nivolumab (3 mg/kg every 2 weeks) until disease progression, unacceptable toxicity, or 12 months of treatment. Nivolumab resulted in significant antitumor activity, prolonged responses, and a good tolerability in patients with advanced cutaneous squamous‐cell carcinoma in the first‐line setting.